Magnetic properties and anisotropy of ultrasound attenuation in APG-832 magnetic liquid - Regulska, Patrycja; Skumiel, Andrzej; Hornowski, Tomasz; Józefczak, Arkadiusz (Archives of Acoustics, 2007)
The results of the ultrasonic and magnetic investigations of APG-832 magnetic liquid are presented. The magnetic measurements were carried out with the aid of a vibrating sample magnetometer (VSM). On the basis of the magnetization curve, the coercive field strength, saturation magnetization and initial susceptibility were evaluated. The attenuation of ultrasonic wave in an APG832 magnetic fluid was studied using the broadband ultrasonic spectroscopy. In the external magnetic field the anisotropy of a sound attenuation was observed. This effect is attributed to the translational and rotational motions of the clusters of the colloidal magnetic particles dispersed in the carrier fluid.